Positive association between proinsulin and fatty liver index in people with type 2 diabetes - Akinobu Nakamura; Aika Miya; Yuka Suzuki; Hiroshi Nomoto; Hiraku Kameda; Kyu Yong Cho; So Nagai; Tatsuya Atsumi (Endocrine Journal)
The post-hoc study, derived from our previous prospective observational study, investigated the association between fasting serum proinsulin levels and hepatic steatosis in people with type 2 diabetes. The severity of hepatic steatosis was assessed using the fatty liver index. A total of 268 participants were divided into three groups: low (n = 110), moderate (n = 75), and high fatty liver index (n = 83). In both the crude and age/sex-adjusted analysis, logarithm-transformed proinsulin was significantly higher in the high fatty liver index group than in the low or moderate groups (all p < 0.01). The moderate fatty liver index group showed higher logarithm-transformed proinsulin than the low group (both p < 0.01). Positive associations between proinsulin and fatty liver index shown in this study would support an involvement of hepato-pancreatic crosstalk in the pathophysiology of type 2 diabetes.